Classification of PD patterns in XLPE cables under various soil conditions using statistical technique - Mansor M.; Ghani A.B.A.; Ghosh P.S. (2023)
Partial discharge (PD) is identified as a main factor contributing to the insulation deterioration in HV equipment including underground cable. This is the first time an attempt has been made to investigate the effect of soil thermal resistivity on PD activities in underground power cables. In this paper, a detailed experiment has been carried out on a simulated set up to study the effect of various soil conditions on the level of PD in an 11 kV, single core, 240mm2 XLPE cable. The PD parameters are measured with the help of Haefely Trench TE 571, PD Measurement System using straight detection method. PD patterns obtained in the form of elliptical waveform are then analysed using statistical techniques. In this paper, the statistical pattern recognition technique has been successfully applied to classify the PD patterns obtained from the experiment under different soil conditions. Thus, classification of PD patterns aims at the recognition of discharges from a particular soil condition. This information is vital for estimating the harmful effect of the thermal property of soil on the level of PD and can lead to decision making like reconditioning of backfill material and adjustment in cable loading.